Econometrics Analysis of Economic Factor Affecting Student Academic Performance Using Correlation and Regression Analysis - B. A Garba; A. D Anyah; E. G Nyong; J. O Delle (Darul Yasin Al Sys, 2026)
This study investigates the relationship between students’ daily feeding times and physical fitness, specifically body weight, using econometric tools such as correlation and regression analysis in a university context. The research aimed to explore the economic and behavioral factors underlying students’ daily eating habits and their potential impact on physical fitness. A sample of 21 students from the Faculty of Science was selected, and data on gender, daily feeding times, and weight were collected. Descriptive statistics, Pearson correlation, and simple linear regression were employed to analyze the data. The results revealed a weak positive correlation between daily feeding time and weight (r = 0.417), indicating no statistically significant relationship, and the regression model showed that only 13% of the variance in students’ weight could be explained by their daily feeding habits. These findings suggest that, within this sample, daily feeding time alone is not a major determinant of physical fitness as measured by body weight. The study concludes that there is no significant link between students’ daily feeding times and their physical fitness and recommends that future research consider broader nutritional patterns, meal frequency, and psychosocial factors such as physical and mental stress to better understand and support healthy weight maintenance among university students.